Kajian Potensi Vegetasi dalam Konservasi Air dan Tanah di Daerah Aliran Sungai (DAS): Studi Kasus di 3 Sub DAS Bengawan Solo (Keduang, Dengkeng, dan Samin) - Maridi, Maridi; Saputra, Alanindra; Agustina, Putri (Prosiding KPSDA, 2015)
Watershed is the land area that could potentially be a source of water. The main components of watershed ecosystem composed of humans, animals, vegetation, soil, climate, and water. Watershed ecosystem components that are interconnected is going to maintain the quality of the watershed. A common problem in a watershed is the sedimentation due to large amounts of waste, landslides, and erosion. Water and soil conservation efforts in the watershed can be cultivated by maintaining the balance of watershed ecosystem components one of which is the condition of the vegetation diversity. This study intends to analyze the potential of vegetation in water and soil conservation in the watershed. In-depth study based on the results of the analysis of vegetation and 3 sub-watershed namely Keduang, Dengkeng, and Samin which is a sub-watershed in the Bengawan Solo watershed. Analysis of the condition of the vegetation around the sub-watershed Keduang, Dengkeng, and Samin shows that vegetation has an important role in maintaining the quality of the watershed. Vegetation affects the ability of soil to retain water, thus increasing soil water reserves, prevent erosion and landslides in the surrounding watershed. Vegetation potentially in favor of water and soil conservation in the watershed are shrub vegetation, grass, and other plant floor coverings.